Optimization of sPEEK/S-TiO2 nanocomposite membranes using response surface methodology for low-temperature fuel cell - Mawlood Maajal Ali; Ali Basem; Anmar Sh Jasim; Dheyaa J. Jasim; Ameer Azam; S.J.A. Rizvi; Yusra A. AlBahadli; Maryam Hussein Abdulameer (Results in Engineering)
Polyether-ether-ketone (PEEK), a speciality thermoplastic polymer is treated with concentrated sulfuric acid to introduce sulfonated repeating units in its backbone. Sulfonated polyether-ether-ketone (sPEEK) is then compounded with sulfonated titanium dioxide (S-TiO2) nanoparticles according to design of experiments (DoE). FT-IR spectra for sPEEK/S-TiO2 nanocomposite membranes show the strong presence of peaks at 3500 cm−1 and 1632 cm−1 wave number because of bending and stretching vibrations of OH-group confirm successful sulfonation of polyether-ether-ketone polymer. Insertion of -SO3H group in polymer backbone hinders the stereo regularity of polymer chains and leads to an amorphous structure as confirmed by X-ray diffraction and transmission electron microscopy of membranes. Thermogravimetric analysis shows that the thermal stability of sPEEK is much poor than its precursor PEEK due to the presence of easily degradable -SO3H groups. Analysis of variance (ANOVA) results show that factor wt.% of S-TiO2 is the most influencing among the factors. The proton conductivity and ion exchange capacity (IEC) increase with wt.% of S-TiO2. Proton conductivity of pristine sPEEK is 31.1 mS/cm which significantly increased to be 60.7 mS/cm for sPEEK/S-TiO2 (0.10 wt%) nanocomposite membrane. IEC, water uptake, and swelling ratio were observed to increase with the addition of S-TiO2 (wt.%) in the sPEEK matrix, reaching values of 62.6 mmol/g, 11.6 %, and 18.6 %, respectively.